Sulglycotide ameliorates inflammation in lipopolysaccharide-stimulated mouse macrophage cells by blocking the NF-κB signaling pathway - Park, Eun Young; Lee, Hyesook; Park, Young Joon; Yang, Jaewook (Immunopharmacology and Immunotoxicology, 2019)
Objective: Several studies demonstrated that sulglycotide has anti-inflammatory and anti-cancer effects. However, the effect of sulglycotide is limited to gastric mucosal tissues and cells and underlying molecular mechanisms are not clear. This study estimated the effect of sulglycotide on lipopolysaccharide (LPS)-induced inflammatory responses in the macrophage cell line, RAW 264.7 and elucidated the molecular mechanisms. Materials and methods: The inhibitory effect of sulglysotide on LPS-induced oxidative stress and inflammatory reactions were determined by Immunofluorescence staining, ELISA, Western blotting and RT-PCR. Results: Our results show that sulglycotide has the ability to inhibit inflammatory mediators and cytokine production as well as reactive oxygen species (ROS) generation. This effect can be the result from regulating the activation of nuclear factor-kappa B (NF-κB) through blocking mitogen-activated protein kinase (MAPK) intracellular signaling pathways. Conclusions: These results indicate that sulglycotide could be an anti-inflammatory and anti-oxidative compound that may be a useful candidate for treatment of inflammatory diseases.
Keywords: Animals; Anti-Inflammatory Agents; Cell Line; Cytokines; Inflammation; Lipopolysaccharides; Macrophages; MAP Kinase Signaling System; Mice; NF-kappa B; RAW 264.7 Cells; Reactive Oxygen Species; Sialoglycoproteins; Signal Transduction; inflammation; lipopolysaccharide; macrophage; reactive oxygen species; Sulglycotide